Morpho-Physiological and Biochemical Responses Of Salt-Sensitive and Salt-Tolerant Potato Varieties To Salinity Stress (Bangladesh Journal of Agricultural Research, 2022)
A pot experiment was conducted with three potato varieties [‘BARI Alu-72’ (salt-tolerant), ‘BARI Alu-25’ (relatively salt-tolerant) and ‘BARI Alu-13’ (saltsensitive)] under three levels of salinity stress (control; 0.2, moderate; 6-8 and severe; 10-12 dSm-1) for evaluating their morphological, physiological and biochemical changes during rabi season of 2018-19. Salinity treatment was imposed from 10 days after emergence (DAE) to maturity stage by adding NaCl solution. Salinity stress caused higher reduction in chlorophyll (Chl), carotenoids (CAR), cell membrane stability index (CMSI), biomass and tuber yield plant-1 but increase in contents of catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX), glutathione peroxidase (GPX), glutathione S-transferase (GST) and glutathione reductase (GR) activities in all potato varieties and at all the salinity levels. The reduction of Chl, CAR, CMSI, biomass and yield plant-1 were lower in ‘BARI Alu-72’ as compared to other two varieties. Moreover, ‘BARI Alu-72’ showed higher activities of CAT, POD, APX, GPX, GR and GST as well as contents of K+ and lower malondialdehyde (MDA), lipoxygenase (LOX) and Na+ contents in comparison with those of ‘BARI Alu-25’ and ‘BARI Alu-13’. Activities of antioxidants were found moderate in ‘BARI Alu-25’. ‘BARI Alu-13’ showed higher Na+ and Na+/K+ ratio. The results showed that salinity tolerance in potato was manifested by lower decrease in biomass and yield plant-1 with higher antioxidant activities and K+ contents, and lower MDA, LOX and Na+ content than salinity sensitive genotype.Bangladesh J. Agril. Res. 45(3): 315-333, September 2020